Peningkatan Kesiapan Kuliah Santri Pesantren Zainul Hasan Melalui Pendekatan Konseling Karir Trait and Factor - Muslihati; Sobri, Ahmad Yusuf; Hotifah, Yuliati; 'Ilmi, Achmad Miftachul; Saputra, Nur Mega Aris (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The COVID-19 pandemic has had a significant impact on education, particularly reducing the readiness of high school students to enter higher education due to the limited availability of career counseling services. This has led to an increasing number of mismatches in university program selections, including among high school students in Islamic boarding schools (pesantren). Therefore, an effective strategy is required to prepare high school students for higher education, especially within the context of the Merdeka Belajar Kampus Merdeka (MBKM) framework. The College Readiness training was conducted at the Zainul Hasan Islamic Boarding School by applying the Trait and Factor counseling approach. A total of 31 high school students were trained to enhance their readiness to enter college, with an additional focus on orienting them to become peer counselors. This blended method training was implemented through five stages: (1) design development, (2) preparation of materials, (3) socialization and pre-test, (4) training implementation, and (5) evaluation and closing. The training materials included topics such as (1) recognizing personal potential, (2) understanding the MBKM program in higher education, (3) recognizing assignment patterns in tertiary institutions, (4) selecting the appropriate major, (5) learning motivation, (6) time management, and (7) coping with exam anxiety. The pre-test and post-test results indicated a significant increase in the students' readiness to enter higher education following the training. Given its importance, it is recommended that counseling teachers engage actively in career guidance to prepare students for higher education within the MBKM framework. Alumni of this training can also be involved in helping other students improve their preparedness for entering higher education.